Nurses' eating habits in Lebanon during the economic and health crises: a cross-sectional study - Rita Georges Nohra; Elissa Naim; Taghrid Chaaban; Monique Rothan-Tondeur (BMC, 2022)
Abstract Background Nurses face multiple stressors that can influence their lifestyle, thus affecting their health status. Scarce are the scientific data on the nutritional status of nurses, especially during health crises. The aim of this study was to assess the impact of the COVID-19 pandemic on the eating habits of hospital nurses in the context of an exceptional economic situation in Lebanon. Methods A cross-sectional study was conducted using a web-based questionnaire, targeting a non-random sampling of frontline nurses using the snowball technique. Descriptive and bivariate analyses were carried out. The population of the study included all registered nurses working in the Lebanese hospitals. A total of 533 nurses completed the questionnaire; 500 surveys were selected after excluding the ones presenting conditions that may affect their eating behavior. Results The majority of the respondents were women (78.6%) with a mean age of 33 years [18-60] [SD,7.44 years]. Most of them (57.6%) had a crowding index ≥1. The consumption of different food groups decreased during these crises. There was a significant correlation between stress and deterioration of healthy food consumption, which provides beneficial nutrients and minimizes potentially harmful elements, especially for meat (OR 2.388, CI 1.463 to 3.898, P < 0.001). The decrease in monthly income showed a real impact on the consumption of healthy food such as meat (OR 2.181, CI 1.504 to 3.161, P < 001), fruits (OR 1.930, CI 1.289 to 2.888, P = 0.001), and milk and dairy products (OR 1.544, CI 1.039 to 2.295, P = 0.031). Conclusions The pandemic and in particular the economic crisis has changed the consumption of healthy food among hospital nurses in Lebanon. Similar research and support may be extended to include other frontline health care workers.